2017
DOI: 10.1073/pnas.1704766114
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided evolution of antigenically distinct adeno-associated virus variants for immune evasion

Abstract: Preexisting neutralizing antibodies (NAbs) against adeno-associated viruses (AAVs) pose a major, unresolved challenge that restricts patient enrollment in gene therapy clinical trials using recombinant AAV vectors. Structural studies suggest that despite a high degree of sequence variability, antibody recognition sites or antigenic hotspots on AAVs and other related parvoviruses might be evolutionarily conserved. To test this hypothesis, we developed a structure-guided evolution approach that does not require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 30 publications
1
145
0
1
Order By: Relevance
“…Multiple reports have demonstrated that natural isolates AAV5 (Zabner et al, 2000), AAV6 (Limberis et al, 2009), and AAV9 (Adam et al, 2014) as well as engineered vectors AAV2.5 (Li et al, 2009) and AAV2.5T (Excoffon et al, 2009) are able to transduce human lung epithelial cells, including primary human airway epithelial (HAE) cultures. Although there is a high prevalence of nAbs against AAVs in the human population, new technologies have been developed to engineer AAV to evade humoral immune responses (Tse et al, 2015(Tse et al, , 2017. These developments potentially allow for the delivery of CoV vaccines or immunotherapeutic directly to the mucosal compartments of the lung.…”
Section: Aav As a Vector For Passive Immunization Against Emerging Covmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple reports have demonstrated that natural isolates AAV5 (Zabner et al, 2000), AAV6 (Limberis et al, 2009), and AAV9 (Adam et al, 2014) as well as engineered vectors AAV2.5 (Li et al, 2009) and AAV2.5T (Excoffon et al, 2009) are able to transduce human lung epithelial cells, including primary human airway epithelial (HAE) cultures. Although there is a high prevalence of nAbs against AAVs in the human population, new technologies have been developed to engineer AAV to evade humoral immune responses (Tse et al, 2015(Tse et al, , 2017. These developments potentially allow for the delivery of CoV vaccines or immunotherapeutic directly to the mucosal compartments of the lung.…”
Section: Aav As a Vector For Passive Immunization Against Emerging Covmentioning
confidence: 99%
“…Fortunately, multiple strategies have been developed to address these hurdles (Tse et al, 2015). For instance, through vector engineering, a new generation of AAV vectors can evade pre-existing nAbs while retaining a good transduction profile in the respiratory system (Li et al, 2009;Tse et al, 2017). For rare genetic diseases, life-long gene expression is important for therapeutic purposes but could cause toxicity.…”
Section: The Challengesmentioning
confidence: 99%
“…Four rAAV1 PTMs within the disordered N-terminal region of the capsid were shared between the human and baculo-rAAV1 vectors: N-terminal acetylation on the initial start methionine, methylation of lysine 61, and phosphorylation on serines 149 and 153. For the remaining residues 217-736 on rAAV1, we detected numerous PTMs within known capsid antigenic motifs that react with known neutralizing antibodies against rAAV1 (456-AQNK-459), (492-TKTDNNNS-499), and (588-STDPATGDVH-597) 27 . One PTM was detected within the 4E4 neutralizing epitope residue (456-459 and 492-498) 28,29 , and several additional PTMs were detected near the 5H7 Here again, HCP impurities were present and different between platforms (Table S6), and Sf9 insect HCP impurities were detected with N-linked glycans ( Table S7).…”
Section: Presence Of Capsid Alterations and Hcp Impurity Levels Are Cmentioning
confidence: 99%
“…Strategies that are currently being evaluated to circumvent pre-existing humoral immunity to AAV vectors are either early in development, ineffective or prone to causing undesirable side effects. These include the engineering of new AAV variants with reduced NAb recognition(18, 19), plasmapheresis or immunoadsorption to reduce the overall levels of circulating antibodies in patient serum prior to AAV administration(20–23), use of capsid decoys(24) or immunosuppression to decrease the B cell population and consequently antibody levels in general(25, 26). While these approaches have demonstrated varying success and efficiency in addressing the problem of circulating antibodies and remain under evaluation, a one-solution-fits-all approach that resolves this challenge is unlikely.…”
Section: Introductionmentioning
confidence: 99%